In vitro and ex vivo gene delivery into proximal tubular cells by means of laser energy: a potential approach for curing cystinuria? - Knoll, Thomas; Sagi, Sreedhar; Trojan, Lutz; Schaaf, Axel; Alken, Peter; Michel, Maurice Stephan (Urological research, 2004)
Cystinuria is the cause of 1-2% of stones observed in adults and about 10% of those occurring in children. Recurrent stone formation and multiple operations cause considerable morbidity. We investigated the transfection efficiency of naked plasmid DNA in porcine kidney cells by applying holmium laser (Ho:YAG) energy in vitro as well as ex vivo in a porcine kidney papilla model. In the in vitro experiments, naked plasmid DNA was added to LLC-PK1 cells suspended in a medium and Ho:YAG laser applied with varying pulses. The transfection efficiency was measured by the expression of EGFP reporter gene in the cells by FACScan analysis and fluorescence microscopy. Ex vivo, papilla from porcine kidney was excised and naked plasmid DNA was added to the tissue in the medium. The laser was then applied and the cryosectioned tissue observed under fluorescence microscope. The efficiency of transfection in vitro significantly improved with the increase in impulses (P<0.01). Transfection at 50 impulses averaged 0.7±0.3%, at 200 impulses 28.3±7.7%, and at 500 impulses 36.1±3.1%. The cell mortality rate increased with higher pulse rate up to 70%. Ex vivo trials showed transfection in extended regions of the tissue and also in the peripheral layers of the papilla. Our study indicates that the transfection of benign kidney cells by Ho:YAG is a promising new gene transfer strategy. The ex vivo trials showed that peripheral renal tissue layers are susceptible to transfection by Ho:YAG applied from the papillary surface.